Calcium isotope composition of marine carbonates from DSDP Hole 90-590B (Table 1) - Fantle, Matthew S; DePaolo, Donald J (Supplement to: Fantle, MS; DePaolo, DJ (2005): Variations in the marine Ca cycle over the past 20 million years. Earth and Planetary Science Letters, 237(1-2), 102-117, https://doi.org/10.1016/j.epsl.2005.06.024, 2005)
A 20 million year marine Ca isotope record is constructed based on measurements of 36 nannofossil ooze samples from DSDP Site 590. The Ca isotopic composition (delta44Ca, relative to our "bulk Earth" average) of carbonate ooze samples varies between -0.2 and -0.9, and the inferred delta44Ca of seawater calcium varies between +1.1 and +0.4 (modern seawater value is +0.95 on our scale). Fluctuations in the seawater Ca isotope ratio occur in 2 to 4 million year intervals and indicate that the supply and removal of Ca from the oceans are seldom in balance. The Ca isotope record is used to reconstruct past weathering fluxes and marine calcium concentrations. The inferred marine concentration of Ca fluctuates by about +/-20% on 2-4 million year time scales and by about +/-50% over the 20 million year record. These variations are presumably superimposed on the previously inferred 100 million year variations. The seawater Ca concentration was about 0.5 times present at 20 Ma and generally increased until 6 Ma (1.7 times present). Local maxima in seawater calcium concentrations occur at 6.4 and 4 Ma, preceding periods of enhanced marine productivity and high mass accumulation rates at Site 590. While the calculated calcium concentrations are sensitive to the assumed d44Ca value for the weathering flux, the 2-4 million year features of the derived curves are not.